PENYELESAIAN SENGKETA NASABAH WANPRESTASI EKONOMI SYARIAH DI PENGADILAN AGAMA MAGELANG - Fatchurohman Fatchurohman; Wilda Nugraismia; Tri Wahyuni; Fahmi Medias (IAIN Surakarta, 2018)
This research is conducted to analyze the implementation of Law no. 50 of 2009 on Religious Court. Based on Supreme Court Regulation (PERMA) Nu. 14 the Year 2016 on Procedures of dispute completion in sharia economic, PERMA Nu. 1 the Year 2014 on Mediation of dispute completion process between sharia financial institution and breach of contract at the Religious Court of Magelang. This research uses the descriptive qualitative method with an empirical juridical approach that is by comparing the rules that have been established with the reality. The result of this research indicates that the Religious Court of Magelang in the process of dispute completion of sharia economic has been in accordance with the mandate of Law Nu. 50 the Year 2009, PERMA Nu. 14 the Year 2016, and PERMA No.1 Year 2014. Until early 2018 the Religious Court of Magelang has been handled 20 cases of dispute breach in sharia economic with the result of 17 cases revoked; 1 case granted, 1 case crossed out, and 1 case still running. The cases handled by the Religious Courts of Magelang are majority dealing with trade with markup (murabahah) of the breach of contract with the reason of problematic financing.